Från behandling till hårdare tag? En kritisk analys av högervågsargumentet inom svensk kriminalpolitik - Robert Andersson (Nordisk Tidsskrift for Kriminalvidenskab)
In this article I address the question of whether there has been a punitive turn in Swedish crime policy or not. Since the punitive turn is connected to the downfall of the rehabilitative ideal, and to what David Garland has termed penal welfarism, I make my argument with reference to these phenomena in Sweden. I claim that there were two rationales behind the penal welfare state and the rehabilitative ideal in Sweden: a social liberal rationale built on paternalism and interventionism, and a social democratic rationale built on Marxist class analysis. My argument is that while penal welfarism is still operating in Sweden, the social liberal rationale has been discarded. This means that the social democratic rationale built on Marxist class analysis is now the single dominating force behind Swedish penal welfarism. The argument for a punitive turn in Sweden therefore has no support.